Deutsches Frauenleben im Wandel der Jahrhunderte - Otto, Eduard, b. 1862 (Historische Quellen zur Frauenbewegung und Geschlechterproblematik, 1909)
A general history of German women, from Germanic times until the 18th-century enlightenment.